Pengaruh Tenaga Kerja, Ekspor, NTP, dan Luas Lahan terhadap PDRB Pertanian di Pulau Jawa - Muhammad Falqi Rahmaddani; Hendry Cahyono (Jurnal Ekonomika : INDEPENDEN, 2026)
The agricultural sector plays a vital role in Indonesia economy, especially in Java Island which contributes 57% of national rice production. This study analyzes the influence of labor, exports, farmer exchange rates (NTP), and rice harvested land area on agricultural sector GRDP in six provinces of Java Island during the 2018-2024 period. Using a quantitative approach with explanatory design, this study applies panel data regression Fixed Effect Model (FEM) using Stata 17 software. Secondary data obtained from Badan Pusat Statistik covers 168 observations (6 provinces × 28 quarters). The results show that exports and NTP have a significant positive effect, harvested land area has a significant negative effect, while labor and the COVID-19 period have no significant effect on agricultural sector GRDP. Simultaneously, all five variables have a significant effect with R² of 74.58%. These findings indicate that the transformation of Java agricultural sector has shifted from physical input expansion towards productivity improvement and diversification of high-value commodities.